To Ban or Not to Ban? A Rapid Review on the Impact of Smartphone Bans in Schools on Social Well-Being and Academic Performance - Tobias Böttger; Klaus Zierer (MDPI AG, 2024)
The effects of smartphone use by children and young people, especially at school, are being discussed around the world. To support this discourse with scientific evidence, this systematic review is guided by the PRISMA framework and examines the effects of smartphone bans in schools on academic performance and social well-being. As a rapid review, it follows a streamlined methodology in order to provide a scientifically sound basis for educational policy decisions as quickly as possible. After a comprehensive database search, five research studies with quantitative results were selected and analyzed, and the effect sizes were calculated in the areas of academic performance and social behavior. The meta-analysis yielded an overall effect size of d = 0.162 (p < 0.05). Smartphone bans have a significant, but modest, effect. This is more pronounced in the domain of social well-being than in the performance domain. Smartphone bans can reduce social problems, such as bullying. The small effect on academic performance might be due to the limited number of studies and effects. We recommend that smartphone bans be introduced in schools, accompanied by educational measures, and evaluated regularly. This can improve the social climate and reduce potential distractions in the classroom. Further research is needed to better understand the long-term effects on academic performance. The aim of a smartphone ban should be to prevent the misuse of these devices, for example, as a tool for bullying classmates, and to prevent their negative impact on learning processes. Alongside the bans, responsible use of the technology and an understanding of its potential should be taught. Ideally, a level of media literacy is achieved that makes a smartphone ban superfluous.